Induced Autophagy of Macrophages and the Regulation of Inflammatory Effects by Perovskite Nanomaterial LaNiO3 - Wei, Yang; Gao, Xuejiao; Zhao, Feng; Baimanov, Didar; Cong, Yalin; Jiang, Yingying; Hameed, Saima; Ouyang, Yixin; Gao, Xingfa; Lin, Xiaoying; Wang, Liming (Frontiers in Immunology, 2021)
Perovskite nanomaterials (NMs) possess excellent physicochemical properties and have promising applications in light-emitting diodes (LEDs), lasers, photodetectors, and artificial synapse electronics. Potential exposure to these NMs happens in the manufacture and application of the perovskite-based products, however, the biological safety of these NMs is still unknown. Here, we used the LaNiO3 NM (LNO), a typical kind of perovskite nanostructures to study the interaction with macrophages (J774A.1) and to explore its biological effects at the cellular level. Firstly, we characterized the properties of LNO including the size, shape, and crystal structure using Transmission electronic microscope (TEM), Dynamic lighting scattering (DLS), and X-ray diffraction (XRD). Secondly, to gain a better understanding of the biological effect, we evaluated the effect of LNO on cell viability and found that LNO induced cell autophagy at a concentration of 5 μg/mL and influenced the inflammatory response based on RT-PCR result. Finally, we demonstrated that the mechanism that LNO causes cell autophagy and immune response is probably due to the metal ions released from LNO in acidic lysosomes, which triggered ROS and increased lysosomal membrane permeation. This study indicates the safety aspect of perovskite NMs and may guide the rational design of perovskite NMs with more biocompatibility during their manufacture and application.